Preclinical hematological profile studies of an ayurvedic medicine Rohitakarista after chronic administration to male Sprague-Dawley rats - Sarker, Arjyabrata; Azad, M. Al; Sikder, M. Mamun; Islam, M. Sazidul; Nidhi, Faria Haque; Jahan, Sharmin; Choudhuri, M. S. K. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Rohitakarista (RHT) is a classical Ayurvedic formulation, traditionally used for the treatment of splenomegaly, particularly among rural populations. Methods: The acute toxicity study of RHT in male Sprague-Dawley rats showed no mortality even at 80 ml/kg body weight. For chronic toxicological evaluation, rats were divided into two groups (n=10 per group). One group received RHT suspension orally at 40 ml/kg body weight daily for 41 consecutive days, while the control group received water. At the end of the treatment period, blood samples were collected to evaluate 25 different hematological parameters. Results: RHT-treated rats showed a significant increase in absolute neutrophil count (153.96%, p=0.05) and neutrophil percentage (84.60%, p=0.04), alongside a significant decrease in lymphocyte percentage (24.62%, p=0.04). Red blood cell count (13.34% decrease, p=0.03), hemoglobin level (12.94% decrease, p=0.04), and hematocrit (14.29% decrease, p=0.01) were also significantly reduced. Non-significant but noticeable changes included increased WBC count (23.80%), eosinophils (216.67%), monocyte percentage (84.06%), and platelet count (17.71%). Other parameters such as MCV, MCH, MCHC, RDW, ESR, bleeding time, clotting time, and platelet indices showed minor and nonsignificant variations. Conclusions: Chronic RHT administration led to significant hematological changes, particularly in neutrophil and erythrocyte indices, suggesting potential immunological and anemic risks. Further biochemical and histopathological studies are recommended to better understand its overall safety profile.